A feasibility study of a best practice health literacy app for Australian adults with chronic kidney disease - Stephanie Zwi; Jennifer Isautier; Angela C. Webster; Kelly Lambert; Heather L. Shepherd; Kirsten J. McCaffery; Kamal Sud; John Saunders; Emma O'Lone; Na Liu; Jinman Kim; Aphra Robbins; et al. (Elsevier, 2022)
Objective: To investigate feasibility of the SUCCESS app; a cross-platform e-health innovation to improve health literacy, self-management and shared decision-making among culturally-diverse Australian haemodialysis patients. Methods: Multi-site, pre-post, mixed-methods study. Haemodialysis patients ≥18 years used the app for 12 weeks. Qualitative data from 18 interviews were thematically analysed to evaluate app acceptability. Quantitative analysis using paired sampled t-tests evaluated feasibility outcomes pertaining to recruitment, retention, data collection and app efficacy (including health literacy; decision self-efficacy; quality of life; behaviour; knowledge; confidence). Results: We successfully recruited diverse participants (N = 116; 45% born overseas; 40% low/moderate health literacy) from four Local Health Districts in Sydney, Australia. However, only 61 participants completed follow-up questionnaires. Qualitative analyses provided insights into acceptability and user engagement. Quantitative analyses showed significant improvements on the health literacy domain 'Ability to actively engage with healthcare providers' (Mean Difference [MD] = 0.2 on a 5-point scale; CI95%: 0.0-0.4; p = 0.03) and decision self-efficacy (MD = 4.3 on a 10-point scale; CI95%: 0.6-7.9; p = 0.02) after 12 weeks app use. Conclusions: The SUCCESS app was feasible and acceptable to participants. The app will be adapted to facilitate ongoing use and engagement among diverse haemodialysis patients. Innovation: This is the first health literacy-informed app to promote active participation in haemodialysis self-management and decision-making, tailored toward culturally-diverse and low health literacy groups.